Exploring The Correlation Between Students' Listening Intensity and Vocabulary Acquisition in EFL Learners Context - Siti Jubaidah; Nisla Jumiati; Ratu Ayu Nurindraswari; Abdul Syahid (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2025)
The study explored the correlation between listening intensity and perceived vocabulary acquisition among EFL learners. Over a two-week period, 20-30 college students recorded their daily listening habits and self-assessed their vocabulary growth through weekly surveys. Listening intensity was measured using daily logs, while vocabulary acquisition was evaluated based on students’ self-reports. Data were analyzed using descriptive statistics and Pearson’s correlation coefficient to determine the relationship between time spent listening and vocabulary gains. The results suggest that higher listening intensity correlates with increased vocabulary acquisition. These findings provide valuable insights for language teachers in developing more effective listening strategies to enhance vocabulary learning.